Essays in Development Economics: Poverty, Religion and Mental Health - Us-Salam, Danish (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2023)
This dissertation includes three standalone chapters, each focused on augmenting our knowledge of three issues in the literature on asset transfers, religion, and mental health. The first essay (Chapter 1) investigates whether a women-targeted asset transfer pro- gram can lift households out of poverty in a post-pandemic context (Sierra Leone). Using a randomized controlled trial, we assess the program’s effects on income, food security, non-food consumption, and asset ownership among the targeted ultra-poor households. Two years after the program, our findings indicate that the program led to significant improvements in these outcomes across the entire sample. How- ever, we observe a larger impact in districts with lower Ebola incidence rates. We attribute this variation in treatment effects to the infrastructural damage and lack of community support caused by the Ebola crisis, which may have constrained the program’s potential in the hardest-hit areas. Our results highlight the importance of considering the local context when designing and implementing asset transfer pro- grams in post-pandemic settings and suggest that complementary efforts to rebuild infrastructure can enhance the effectiveness of such interventions. The second essay (Chapter 2) studies the health effects of religious practices in the month of Ramadan, one of the central pillars of Islam. Ramadan requires Muslims to fast daily from dawn to sunset and thus may have physiological and psychological consequences. To establish causality, we use two rounds of a large-scale survey in Bangladesh and exploit the variation in the day on which households were interviewed. This paper reports four main results: (i) households decrease aggregate consumption levels across all income groups, (ii) Ramadan serves as a negative health shock which is larger in absolute terms for households in the bottom 50% of wealth consequently pushing them closer to the WHO malnourished guideline, (iii) the adverse health shock on households isn’t translated into a similar shock for children under 5 in the same households and (iv) finally a net zero effect on subjective well-being. Together, our results suggest that voluntary adherence to religious practices changes individual behavior in ways that have negative implications for physiological health but no implications for psychological health. The third essay (Chapter 3) investigates adolescent girls’ mental health in Uganda during the COVID-19 pandemic. The paper adds to the existing evidence base by drawing on 3 rounds of panel data (2019–2021) to assess changes in adolescent mental health among 468 young women aged 13–19 years residing in rural to semi-urban villages in Uganda before and during the pandemic. Using fixed effects models, we find increases in symptoms of moderate-to-severe depression as measured by both the Patient Health Questionnaire-8 during the pandemic and accompanying lockdown measures. We also find that adolescent girls who faced a higher COVID-19 burden exhibit stronger declines in mental health. Our findings shed light on the impacts of the pandemic on young women’s mental health in an LMIC context and suggest the need for age-, gender-, and vulnerability-targeted policies that ensure that the pandemic does not undo current progress toward a more gender-equitable world.
APPROVED
Keywords: Religion; Mental Health; Poverty